Perceptions and Experiences of Nursing Students in Caring for People Living with HIV/AIDS in South Africa: A Qualitative Study - Ruwadzano Dorcas Mabhiza; Varshika Bhana; Heather Sedibe (Nurse Media: Journal of Nursing)
Background: Although previous studies focusing on nurses’ perceptions of caring for people living with HIV (PLHIV) have been conducted in numerous countries, little is known about first-year student nurses’ perceptions and experiences regarding their role in caring for PLHIV in South Africa. To ensure quality care for PLHIV, it is essential to explore first-year student nurses’ roles in caring for PLHIV.